Ireland : Financial Sector Assessment Program: Technical Note-Stress Testing the Banking System. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This Technical Note discusses the results of the stress testing carried out to examine the banking system in Ireland. These tests examined the resilience of the Irish banking system to solvency, liquidity, and contagion risks. The results revealed several sources of vulnerability, although these remain manageable at the macro level. The global liquidity stress tests reveal that some banks in the system would be exposed to liquidity risks in the event of large deposit withdrawals, under a more severe scenario than the Basel III Liquidity Coverage Ratio metrics. By contrast, additional counterbalancing capacity would allow banks to cope with net outflows in every maturity bucket.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet